Students' perspectives on literary texts used in Malaysian ESL classroom / Nur Darina Mohd Salleh - Mohd Salleh, Nur Darina (2015)
Literature was introduced in the Malaysian ESL classrooms with the aspiration to develop proficiency in the learners with adequate capacity to respond personally to literary texts provided by the English syllabus besides interpreting and appreciating the texts appropriately and instil the love for reading and improve language acquisition. In 2010, a new set of literary texts were introduced in the ESL classroom. Therefore, the aim of this study is to explore Form Four students' perspectives of the literary texts with regards to layout, content and language used in the texts. Specifically, the study examined the perspectives based on the variables such as gender and locality of the school. This study employed a mixed- method approach using both qualitative and quantitative instruments such as a questionnaire and semi - structured interviews. This study involved a total of 80 Form Four students of which 45 students were from an urban school while the remaining 35 students were from a rural school. Both schools were located in the district of Kota Setar, Kedah. The two teachers teaching literature in the two selected ESL classrooms were also involved in the study. Overall, the findings show that majority of students think that the literary texts have encouraged them to read more English books, the topics discussed are interesting and varied but they also think that current literary texts are biased towards western culture. They also felt that the language was rather difficult. With regards to layout, students pointed out that the text is well organized with appropriate use of print size and font and they felt that the layout is interesting as it helped them to visualize the context of the story, poem or drama. Furthermore, the findings revealed that a majority of students are able to relate to the moral values in the texts but felt that the issues discussed in the texts were rather adult and hence they could not relate well to them. The findings further showed that a majority of the students felt the language used was good, accurate and precise and could help them to improve their language proficiency. The urban students' felt that the vocabulary is within their level of proficiency but the rural student' felt the vocabulary used in the text is rather difficult and beyond their grasp. Additionally, the findings also showed that there was no significant difference in students' perspectives of literary texts with regards to layout, content and language used based on gender and locality of the schools. These findings imply that ESL teachers and other stake holders should assist the students to build a strong foundation of understanding the current texts so that the students will be more prepared and confident to learn and understand the texts. Considering all the challenges faced by the students when dealing with the texts in ESL classroom such as failing to interpret and analyse the text, feeling that there is no linkage between learning literature and ESL learning and could not relate well with past experiences, it is helpful if the stakeholders could select appropriate texts for the students' based on their language proficiency, gender,background knowledge and locality of the school. Finally, it can be said that there is still room for improvement in ensuring that the literary texts will give benefits for both teachers and students alike.